P079 Using theory and evidence to optimise an accelerated partner therapy intervention in a chlamydia partner notification trial. (14th July 2019) - Flowers, Paul; Pothoulaki, Maria; Owusu, Melvina; Vojt, Gaby; Mapp, Fiona; Mercer, Catherine; Cassell, Jackie; Saunders, John; Wayal, Sonali; Symonds, Merle; Nandwani, Rak; Howarth, Alison; et al.
Abstract : Background: Accelerated Partner Therapy (APT) is a method of partner notification (PN) which includes remote assessment, self-sampling and treatment of the sex partner(s) of a person diagnosed with STIs. Using the Behaviour Change Wheel approach, we sought to understand, and then systematically moderate, the psychological and behavioural challenges involved in delivering and receiving APT as part of LUSTRUM, a UK-based chlamydia PN trial. Methods: We conducted 11 focus groups with patients (n=30) and the public (n=26), and five focus groups with healthcare professionals (n=30) involved in PN. Initial thematic analysis explored the barriers and facilitators to each essential and sequential step in APT, from the perspective of each role in this interpersonal, relay intervention. Further analysis specified a series of theoretically based, and evidence-informed approaches that can be used to methodically reduce the various barriers to uptake and implementation of APT Results: Active, intervention components that can enhance staff delivery, index patient and sex partner uptake of APT included providing: clearer information for all about the overall sequential steps involved in APT (highlighting shared roles and responsibilities); a stronger focus upon what healthcare professionals, index patients and their sex partners should do in relation to each step of APT, including written checklists for staff and index patients; essential messages supporting PN and self-management of sex partners engaging in APT; pertinent information about why to engage in APT (in relation to considering key consequences). Conclusion: This is the first study to provide evidence-based and theoretically informed approaches to enhance contemporary PN. These findings informed the development of an intervention manual, training resources for staff and online video materials. Together, these materials detail, in highly specific and replicable ways, the optimal methods to reduce barriers to implementation of APT and utilise factors that facilitate implementation thereby potentially improving PN outcomes for chlamydia. Disclosure: No significant relationships.